2020
DOI: 10.1098/rsos.192080
|View full text |Cite
|
Sign up to set email alerts
|

Our dreams, our selves: automatic analysis of dream reports

Abstract: Sleep scientists have shown that dreaming helps people improve their waking lives, and they have done so by developing sophisticated content analysis scales. Dream analysis entails time-consuming manual annotation of text. That is why dream reports have been recently mined with algorithms, and these algorithms focused on identifying emotions. In so doing, researchers have not tackled two main technical challenges though: (i) how to mine aspects of dream reports that research has found important, such as charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…This data is in line with what emerged from a longitudinal study by Pesant and Zadra (2005), who demonstrated that psychological wellbeing is inversely correlated with dream content characterised by aggressive interactions, negative emotions and episodes of failure. In fact, according to the perspective that regards dream material as a continuity with daytime material, the content of dreams reflects what is experienced in everyday life (Domhoff, 1996;Domhoff, 2003;Fogli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This data is in line with what emerged from a longitudinal study by Pesant and Zadra (2005), who demonstrated that psychological wellbeing is inversely correlated with dream content characterised by aggressive interactions, negative emotions and episodes of failure. In fact, according to the perspective that regards dream material as a continuity with daytime material, the content of dreams reflects what is experienced in everyday life (Domhoff, 1996;Domhoff, 2003;Fogli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This result is confirmed in the literature, since a hypothesis, now widely accepted and complementary to the continuity hypothesis, maintains that the dream is a time when thought continues, albeit in a different state of consciousness, leading, through the development of problemsolving strategies, to solutions to problems faced in everyday life (Barrett, 2017). From this point of view, dream activity probably allowed the population to recover and re-process the emotions and experiences encountered during the pandemic reality, then identifying the most effective strategies to respond adaptively to the stress of the pandemic reality (Fogli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility was already illustrated by a series of studies by Bulkeley [ 57 , 59 , 60 ], who successfully identified some of the dream themes that are normally assessed through manual scoring by exploring dreams collected in dream databases using predefined sets of terms related to different categories of interest. More recently, Fogli and colleagues developed and validated a more advanced tool combining syntactic analysis with a dictionary-based approach [ 77 ]. In particular, the authors focused on three specific Hall and Van de Castle’s categories (“characters”, “interactions”, and “emotions”) and designed a dictionary-based tool that recognizes linguistic items recurring in dream reports as referring to specific entities of interest.…”
Section: Automated Methods For Replacement Of Manual Ratingsmentioning
confidence: 99%
“…The hypothesis postulates that dreams are a continuation of our waking experiences, especially of those that trigger vivid emotions. It was first formulated by psychologist Calvin Hall in the 190s, and, in the following decades, it has been extensively studied [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%